Giardia duodenalis in small animals and their owners in Germany: A pilot study. (20th November 2018) - Rehbein, Sina; Klotz, Christian; Ignatius, Ralf; Müller, Elisabeth; Aebischer, Anton; Kohn, Barbara
Abstract: Giardia duodenalis is a relevant gastrointestinal protozoan pathogen of humans and animals. This species complex consists of eight genetically different assemblages. Assemblages A and B are pathogenic to humans and pets, thus confer zoonotic potential. The risk of zoonotic transmission has been controversially discussed. The aim of this monocentric cross‐sectional pilot study was to investigate G. duodenalis assemblages in humans and pets living in common households in Berlin/Brandenburg (Germany). Samples from dogs, cats and humans sharing the same households were screened for Giardia infection by antigen‐detecting assays. All human samples were additionally analysed by a Giardia ‐specific qPCR. Cyst quantification and sequences of different gene loci (triosephosphate isomerase ( tpi ), glutamate dehydrogenase ( gdh ), β‐giardin ( bg ) and for dogs SSUrDNA) were analysed. A total of 38 households (31 households with dogs and seven with cats) with 69 human individuals participated in the study. Initial antigen‐detecting assays revealed Giardia‐ positive results for 13 (39%) canine, one (14%) feline and one human sample. Reanalysis of the human samples by qPCR revealed two more positive specimens (4%). Two of these three samples were identified as assemblage B at all tested loci. Success rate of assemblage typing for pet samples was generally low and comprised mainly the SSUrDNA locus only. Overall, six of 13 Giardia ‐positive canine samples were typable (2× A, 1× co‐infection: A and B, 1× C; 2× D). One pair of samples (dog and human) from the same household had a similar but not identical assemblage B sequence at tpi locus. Assemblage A was also detected in the dog specimen, which hampered sequence analysis. In conclusion, although exhibiting limitations due to the sample size, our study highlights the need for better and standardized typing tools to distinguish G. duodenalis strains with higher resolution in order to perform proper case–control studies for a realistic estimation of zoonotic risk.